Would an Understanding of Entrepreneur’s Ethical Mindset Lead to a Theorization of‘Entrepreneurship Ethics’?: A Research Idea - Issa, Theodora; Geneste, Louis; Pick, David; Weber, Paull (Australian and New Zealand Academy of Management (ANZAM), 2012)
The aim of this paper is to enable a better understanding of ethics in relation to entrepreneurs and entrepreneurship. This paper identifies gaps in theory and research. This paper responds to the calls in the literature for a careful study of ‘entrepreneurship’ its complex business activity and the ethical implications. To this end an application of the ‘ethical mindsets’ framework is suggested to be employed to generate a better understanding of this relationship and the enhancement of the theorization of ‘entrepreneurship ethics’. This paper provides new opportunities for research that have the potential to generate fresh appreciation of the importance of ethics, and specifically ‘ethical mindsets’ to entrepreneurs and entrepreneurship that will assist researchers and practitioners to enhance knowledge and develop better and more ethical practices.